2019
DOI: 10.1017/s1047951119001173
|View full text |Cite
|
Sign up to set email alerts
|

Salusin-α levels are negatively correlated with diastolic blood pressure in children with obesity

Abstract: Salusins have emerged as a new biomarker that reflects an increased inflammatory state, which is associated with cardiovascular risk. We investigated the predictive value and usefulness of salusins as an inflammatory biomarker in obese children. This prospective cohort study included 75 obese children and 101 healthy children (as a control group). Salusin-α, Salusin-β, and various cardiovascular parameters were assessed in both groups. Correlation analyses of Salusin-α and Salusin-β with body mass index standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Salusins are being interested as a novel biomarker of in ammatory state (30). As far as we know, the current study for the rst time demonstrated that salusin-α treatment could inhibit gene expression and enzyme activity of MMP-2 and MMP-9 in HUVECs.…”
Section: Discussionmentioning
confidence: 57%
“…Salusins are being interested as a novel biomarker of in ammatory state (30). As far as we know, the current study for the rst time demonstrated that salusin-α treatment could inhibit gene expression and enzyme activity of MMP-2 and MMP-9 in HUVECs.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, it correlated positively with the body mass index Z-score and triglyceride levels [ 45 , 46 ]. In another study, salusin-α correlated negatively with diastolic blood pressure; however, no significant differences were found between normal-weight and overweight children [ 47 ]. Similarly, both of the salusins are useful in training effectiveness, demonstrating a significant improvement of both markers in aerobic and high-intensity interval training [ 48 ].…”
Section: Salusin-α and -βmentioning
confidence: 99%
“…Salusin-α and -ß are involved directly in the process of atherosclerosis with salusin-α slowing down and salusin-ß promoting atherosclerosis. In children, salusin-α correlated negatively with diastolic pressure [50,51]. Adropin was discovered recently as a regulator of endothelial function among its several other physiological roles, such as angiogenesis, metabolism of glucose, fatty acids and dyslipidemia.…”
Section: Future Perspectivesmentioning
confidence: 99%